Effectiveness of Modern Wound Dressing on the Growth of Staphylococcus Aureus Bacteria - Gito, Gito; Rochmawati, Erna (Jurnal Keperawatan, 2018)
Wounds are classified as acute and chronic. The early stage of chronic wound formation are characterized by the emergence of gram-positive and gram-negative organisms. such as Staphylococcus aureus and Escherichia coli. At a later stage, Gram-negative Pseudomonas species tend to attack the inner layers of the wound. Modern wound dressings containing antimicrobials that have been developed since the last twenty years. It is effectively to kill bacteria and fungi in the wounds and to prevent recurrent infections during wound healings. The purpose of this paper is to report the results of a review that focuses on the effect of modern wound dressing on Staphylococcus aureus bacteria. Relevant articles were searched in PubMed and google’s scholar using keywords "modern wound dressing", "antibacterial", "staphylococcus". Ten articles that fit with the inclusion criteria were included in this review. The results show Modern wound dressing with antimicrobial content can inhibit bacterial growth. Interm of time and type of bactreria. Thus, this literatures review can be the basis for further researchs on the effectiveness of modern wound dressings against Staphylococcus aureus.